An introduction to Judaism - De Lange, N. (Introduction to religion, 2000)
Beginning with the question 'who is a Jew?', this book offers a lucid account of Judaism and the Jewish people. Written for Jews and non-Jews alike, be they students, teachers, or general interested readers, the book brings out the extraordinary richness and variety of Judaism: its historical depth, and the vigour and at times amazing endurance of its traditions - in the home, in the synagogue, in its literature, in individual and community life. Nicholas de Lange explains the history and details of inherited rituals and customs; of established religion; of concepts such as Zionism, Diaspora, Messianism. Half of the world's Jews live in North America and the rest are widely scattered, and the book is sensitive to the global context of Judaism. An Introduction to Judaism contains illustrative tables and maps, a full glossary, chronology, bibliography and index. This is a stimulating and comprehensive introduction to a major world culture.